Vascular underpinning of COVID-19 - Wazny, Vanessa (2021)
COVID-19 management guidelines have largely attributed critically ill patients who develop acute respiratory distress syndrome, to a systemic overproduction of pro-inflammatory cytokines. Cardiovascular dysfunction may also represent a primary phenomenon, with increasing data suggesting that severe COVID-19 reflects a confluence of vascular dysfunction, thrombosis and dysregulated inflammation. Here, we first consolidate the information on localized microvascular inflammation and disordered cytokine release, triggering vessel permeability and prothrombotic conditions that play a central role in perpetuating the pathogenic COVID-19 cascade. Secondly, we seek to clarify the gateways which SARS-CoV-2, the causative COVID-19 virus, uses to enter host vascular cells. Post-mortem examinations of patients' tissues have confirmed direct viral endothelial infection within several organs. While there have been advances in single-cell RNA sequencing, endothelial cells across various vascular beds express low or undetectable levels of those touted SARS-CoV-2 entry factors. Emerging studies postulate alternative pathways and the apicobasal distribution of host cell surface factors could influence endothelial SARS-CoV-2 entry and replication. Finally, we provide experimental considerations such as endothelial polarity, cellular heterogeneity in organoids and shear stress dynamics in designing cellular models to facilitate research on viral-induced endothelial dysfunctions. Understanding the vascular underpinning of COVID-19 pathogenesis is crucial to managing outcomes and mortality.